Imaging following thermal ablation of early lung cancers: expected post-treatment findings and tumour recurrence. Issue 11 (November 2021) - Das, J.P.; Barry, C.; Schöder, H.; Camacho, J.C.; Ginsberg, M.S.; Halpenny, D.F.
Abstract : Thermal ablation is a minimally invasive technique that is growing in acceptance and popularity in the management of early lung cancers. Although curative resection remains the optimal treatment strategy for stage I pulmonary malignancies, percutaneous ablative treatments may also be considered for selected patients. These techniques can additionally be used in the treatment of oligometastatic disease. Thermal ablation of early lung tumours can be achieved using several different techniques. For example, microwave ablation (MWA) and radiofrequency ablation (RFA) utilise extreme heat, whereas cryoablation uses extremely cold temperatures to cause necrosis and ultimately cell death. Typically, post-ablation imaging studies are performed within the first 1–3 months with subsequent imaging performed at regular intervals to ensure treatment response and to evaluate for signs of recurrent disease. Surveillance imaging is usually undertaken with computed tomography (CT) and integrated positron-emission tomography (PET)/CT. Typical imaging findings are usually seen on CT and PET/CT following thermal ablation of lung tumours, and it is vital that radiologists are familiar with these appearances. In addition, radiologists should be aware of the imaging findings that indicate local recurrence following ablation. The objective of this review is to provide an overview of the expected post-treatment findings on CT and PET/CT following thermal ablation of early primary lung malignancies, as well as describing the imaging appearances of local recurrence.